PENGARUH ORIENTASI PASAR TERHADAP KEUNGGULAN BERSAING MELALUI INOVASI PADA UKM BIDANG FURNITURE DI KOTA SEMARANG - Nurseto, Sendhang (JURNAL ILMU SOSIAL, 2014)
One of the small and medium enterprises in the city of Semarang is the field of furniture and furniture . Furniture or furniture that is often referred to as a product included in the household so that the furniture is not the scarce goods but is needed by the community . Realization of production every year to reach an average of only 90 % of the target . The resulting production also fluctuated every year , almost every year has decreased . The purpose of this study was to determine the effect of market orientation and innovation to compete SMEs lead with furniture in the city of Semarang . The population in this study was 64 furniture craftsman whose products have been exported to SMEs furniture Semarang . Way of selecting a sample ( respondents ) were used in this study using nonprobability sampling technique. Analysis using quantitative , qualitative analysis , validity , reliability testing , path analysis , descriptive analysis and differential analysis .The results showed t value of the variable effect of market orientation on innovation by 3.690 , the hypothesis 1 ( H1 ) that the Market Orientation proven positive effect on innovation . T value of the variable effect of market orientation on Competitive Advantage of 2,079 > t Table , hypothesis 2 ( H2 ) that the positive effect on market orientation Competitive Advantage proven . T value of the variable influence of Innovation for Competitive Advantage 3.332 > t table , the hypothesis 3 ( H3 ) that innovation has a positive effect on Competitive Advantage proven . Calculated F value of the variable influences Market Orientation and Innovation for Competitive Advantage by 9.396 > F table , hypothesis 4 ( H4 ) that the Market Orientation and Innovation positive effect on Competitive Advantage proven .Craftsmen will need to improve understanding of market orientation in the face of competition . Owned and increase innovation to improve the ability and skill to produce a better product thus increasing the competitive advantage of products.